(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Systemic lupus erythematosus is a chronic autoimmune disease that predominantly affects women of reproductive age, making pregnancy management a major clinical concern. Pregnancy in patients with systemic lupus erythematosus is associated with an increased risk of maternal, fetal, and neonatal complications resulting from immune dysregulation, vascular involvement, and organ damage. Disease activity at conception, lupus nephritis, antiphospholipid syndrome, and cardiopulmonary involvement are among the principal factors contributing to adverse pregnancy outcomes. Maternal complications frequently include disease flares, hypertensive disorders, renal deterioration, and thromboembolic events, while fetal complications encompass pregnancy loss, intrauterine growth restriction, preterm delivery, and neonatal lupus manifestations. Evidence indicates that favorable pregnancy outcomes are more likely when conception occurs during periods of disease remission or stable low activity. Comprehensive preconception evaluation, individualized risk stratification, and close multidisciplinary monitoring throughout pregnancy and the postpartum period are essential for minimizing complications. An integrated clinical approach allows many women with systemic lupus erythematosus to achieve successful pregnancy outcomes despite the high-risk nature of the condition.